PENGARUH MOBILISASI DINI DENGAN MOTOR RELEARNING PROGRAM TERHADAP FUNGSIONAL EXTREMITAS ATAS PASIEN STROKE ISKEMIK - Utami Gaswi; Nia Kurniawati; Achwan Achwan (Ikatan Fisioterapi Indonesia cabang kota bekasi, 2023)
ABSTRACT Background : Stroke is one of the neurological disorders that is the main cause of the main task in the world. increase the independent ability of the upper extremities a large increase in functional disability that affects a person's quality of life and independence. Motor relearning program (MRP) is a physiotherapy method that can be used for patient mobilization exercises in the acute phase. Early mobilization in acute ischemic stroke has been carried out and has shown good results in increasing the functional ability of the upper extremities. Research Methods : This research method uses a pre-experimental with one group pre-posttest which is carried out in the inpatient room of the National Brain Center (NBC) Hospital. Determination of the sample using the Lameshow formula and obtained 14 samples were selected based on the inclusion criteria. Upper extremity functional measurements were performed using the Chedoke Arm and Hand Activity Inventory (CAHAI) on baseline and final data after the intervention 2 times a day during the 5-day hospitalization phase. Results: Paired T-Test test on quality of life before and after the intervention obtained a value of P = 0.000 (p<0.05). Conclusion: There is an effect of early mobilization with a motor relearning program on improving the quality of life of acute stroke patients at NBC Hospital